Exploring the Relationship between Biologics and Postoperative Surgical Morbidity in Ulcerative Colitis: A Review - Quaresma, Abel Botelho; Barbosa Barauna, Fernanda da Silva; Teixeira, Fabio Vieira; Saad-Hossne, Rogerio [UNESP]; Kotze, Paulo Gustavo (Mdpi, 2021)
Background: With the paradigm shift related to the overspread use of biological agents in the treatment of inflammatory bowel diseases (IBD), several questions emerged from the surgical perspective. Whether the use of biologicals would be associated with higher rates of postoperative complications in ulcerative colitis (UC) patients still remains controversial. Aims: We aimed to analyze the literature, searching for studies that correlated postoperative complications and preoperative exposure to biologics in UC patients, and synthesize these data qualitatively in order to check the possible impact of biologics on postoperative surgical morbidity in this population. Methods: Included studies were identified by electronic search in the PUBMED database according to the PRISMA (Preferred Items of Reports for Systematic Reviews and Meta-Analysis) guidelines. The quality and bias assessments were performed by MINORS (methodological index for non-randomized studies) criteria for non-randomized studies. Results: 608 studies were initially identified, 22 of which were selected for qualitative evaluation. From those, 19 studies (17 retrospective and two prospective) included preoperative anti-TNF. Seven described an increased risk of postoperative complications, and 12 showed no significant increase postoperative morbidity. Only three studies included surgical UC patients with previous use of vedolizumab, two retrospective and one prospective, all with no significant correlation between the drug and an increase in postoperative complication rates. Conclusions: Despite conflicting results, most studies have not shown increased complication rates after abdominal surgical procedures in patients with UC with preoperative exposure to biologics. Further prospective studies are needed to better establish the impact of preoperative biologics and surgical complications in UC.
Keywords: ulcerative colitis; antibodies; monoclonal; postoperative complications; infections; necrosis tumor factor-alpha; integrins